Growth parameters of InAs/GaAs quantum dots grown by MOVPE - Zulkafli Othaman, author; Shahrizar Roslan, author; Lim, Kheng Boo, 1981-, author; Rosnita Muhammad, 1972-, author; Regional Conference Solid State Science & Technology (23rd : 2007 : Johor Bahru) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL